Simulation and Analysis of Modified DTC of PMSM - D.Kiran Kumar; G.Tulasi Ram Das (Institute of Advanced Engineering and Science, 2018)
This research paper describes the simulation and analysis of the modified DTC for Surface mounted Permanent Magnet Synchronous Motor (SPMSM) using PI controller. Among all of the various drive systems,PMSM is widely used for accurate speed and torque control, with greater efficiency, superior torque to inertia and high power density.The Conventional DTC secheme widely used for this purpose but it is failed to achieve desirable performance of the system for which the modified DTC secheme is propsed.The modified DTC algorithm controls the voltage vectors, directly from a simple look up table depending on outcome of the torque and indirectly flux controllers.The overall drive system can be implemented in SIMULINK/MATLAB environment.The modified DTC is validated with loading conditions.The simulated results are focused on the speed, settling time at loaded conditions, torque and flux linkages ripple and THD in the phase current for modified DTC applied to SPMSM.